Perencanaan Manajemen Seni Pertunjukan Ubud Village Jazz Festival - I Gde Made Pandu Vijayantara Putra; Putu Sandra Devindriati Kusuma (Institut Seni Indonesia Denpasar, 2023)
Purpose: This article aims to find out how to plan the management of performing arts at the Ubud Village Jazz Festival. Management is the main thing in every performing arts performance starting from pre-production to post-production. Method: The method used in this writing is a qualitative method with a descriptive presentation. Data obtained by interviews and literature review, which will then be analyzed through triangulation from raw data collection, selection, processing to drawing conclusions. Results and discussion: The Ubud Village Jazz Festival was made out of concern, where the founder felt that there was a period of jazz music that had been forgotten and caused the loss of the true identity of jazz music. The findings in this article show that management planning is carried out by setting goals, designing budgets, looking for sponsors by looking at previous year's activities, making timelines, deadlines, job descriptions, hiring outsourcing and recruiting volunteers to support the achievement of the goals of UVJF activities. Implication: Good management planning for the Ubud Village Jazz Festival is also a means to educate the public about jazz music, help the economy of the surrounding community in Ubud, and more than that to show the identity of the jazz festival.